2001
DOI: 10.14411/fp.2001.018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of Atlantic salmon (Salmo salar) with marine Eubothrium sp. (Cestoda: Pseudophyllidea): observations on the life cycle, aspects of development and growth of the parasite

Abstract: Abstract. The life cycle of marine Eubothrium sp. (Cestoda: Pseudophyllidea), from Atlantic salmon (Salmo salar L.) was experimentally completed in one year and included only one intermediate host (Acartia tonsa Dana) (Copepoda: Calanoida). Adult cestodes were collected from farmed salmon, and ripe eggs released by the cestodes were fed to Acartia tonsa. Ingested eggs hatched in the gut and the larvae developed in the haemocoel of the copepod for 15 days at 16°C. A total of 170 seawaterreared salmon were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…They suggested that increased growth and maturation of Eubothrium sp. in large hosts could reflect an increased availability of nutrients as larger fish are metabolically more active (Saksvik et al , 2001). Because larger Atlantic salmon are metabolically more active, they are likely to catch more prey per unit effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that increased growth and maturation of Eubothrium sp. in large hosts could reflect an increased availability of nutrients as larger fish are metabolically more active (Saksvik et al , 2001). Because larger Atlantic salmon are metabolically more active, they are likely to catch more prey per unit effort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, larger Atlantic salmon contained higher percentages of lipids than did smaller fish. Saksvik et al (2001) found that individuals of Eubothrium sp. that inhabited larger Atlantic salmon were longer than cestodes inhabiting smaller fish.…”
Section: Discussionmentioning
confidence: 99%
“…The infection procedure with Eubothrium sp. is described in Saksvik, Nylund, Nilsen & Hodneland (in press) where further details on rearing conditions of the experimental fish are also given. The fish were fed 50% of the amount recommended by the feed company to avoid overfeeding, and hence the possibility of concealing effects of the cestode.…”
Section: Methodsmentioning
confidence: 99%
“…It is also vital that only fresh material is used for comparative studies, because the eggs readily collapse when processed and prepared as permanent mounts (see Table 4). Members of E. crassum are most probably of marine origin, but can complete their life cycle in fresh or brackish water (Rosen 1919; Kennedy 1978; Saksvik et al 2001; Hanzelová et al 2002). This is supported by the experimental cross‐infection of marine copepods with eggs taken from gravid worms from freshwater hosts and vice versa (Hodneland & Solberg 1995; present study).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudophyllidean tapeworms of the genus Eubothrium NYBELIN 1922 are common parasites of fish in Europe and North America (Nybelin 1922;Andersen & Kennedy 1983;Hoffman 1999). The life cycles of Eubothrium crassum BLOCH 1779 and Eubothrium salvelini SCHRANK 1790 have been comprehensively studied (Rosen 1919;Vik 1963;Boyce 1974;Kuperman 1978;Saksvik et al 2001;Hanzelova´et al 2002), whereas only a single study by Kuperman (1974) has looked at Eubothrium rugosum BATSCH 1786. Kuperman (1978) andHanzelova´et al (2002), using egg dimensions, found interspecific differences between E. crassum and E. salvelini.…”
mentioning
confidence: 99%